No accounting for greed - BBC worldwide ([Australia : BBC Worldwide, 2002)
Report on the failure of American accounting firm Arthur Andersen to properly audit and detect fraudulent practices in the accounts of its powerful clients, resulting in the huge financial collapses of companies such as Enron and WorldCom
Title from title screen
Originally broadcast on the BBC television program Money programme
DVD format
Keywords: Arthur Andersen (Firm); Accounting firms -- Corrupt practices -- United States